Piranhas - Grossman, Susan M. (New York : Dillon Press ; Toronto : Maxwell Macmillan Canada ; New York : Maxwell Macmillan International, 1994)
Describes the physical characteristics, habitat, and life cycle of piranhas, and explains that their scary reputation may be exaggerated.
Includes index.
School Library Journal
Horn Book
6.1
3-6
Keywords: Piranhas -- Juvenile literature; Piranhas; Piranhas